Effect Of Rupiah Exchange Rate Fluctuations And Inflation On Stock Index Volatility In Indonesia: A Comparative Study Of Sharia Vs. Conventional - Niam, Muh Imdaadun; Febrilyantri, Candra (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the impact of exchange rate fluctuation (JISDOR) and inflation on the volatility of stock indices in Indonesia using the Panel Autoregressive Distributed Lag (Panel ARDL) approach with the Pooled Mean Group (PMG) estimation method. The research focuses on the Composite Stock Price Index (IHSG) and the Indonesia Sharia Stock Index (ISSI) from January 2020 to March 2025 using monthly data . The results show that JISDOR fluctuations have a significant positive effect on index volatility in both the short and long run. Inflation has a positive effect in the short run but reveals a negative long-run relationship. IHSG is more sensitive to exchange rate movements, while ISSI exhibits a stronger response to inflation. The significant error correction term confirms a robust adjustment mechanism toward long-run equilibrium. These findings underline the importance of macroeconomic stability for a resilient capital market and emphasize the role of sharia indices as a relatively stable investment alternative, albeit still responsive to macroeconomic shifts. This study provides practical implications for investors and policymakers in formulating strategies to strengthen the stock market amid global economic uncertainties.